Identification based on a finite element model of an impact force occurring on a composite structure - El-Bakari, Abdelali; Khamlichi, Abdellatif; Hanafi, Issam (Zielona Góra: Uniwersytet Zielonogórski)
Based on the inverse approach and the finite element method, the quality of a reconstructed signal is discussed in this work. The responses caused by a distributed impact on a portion of a composite structure can be recovered using dynamic analysis. The structure is thought to be complex and made up of two different-sized plates made of two different materials.
Keywords: inverse problem; modal analysis; identification; impact force; composite structures